Correlation between Waist Circumference and IGF-1 Levels in an Elderly Population in Bali, Indonesia - Dwipayana, I Made Pande; Gotera, Wira; Saraswati, Made Ratna; Semadi, I Made Siswadi; Nugraha, Ida Bagus Aditya; Suastika, Ketut; Gde Budhiarta, Anak Agung; Amrita, Padma; Putra, Wahyu Pratama (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Background. Hyperinsulinemia due to insulin resistance is hypothesized to act as a promotor of cancer growth. In addition to the direct effects of hyperinsulinemia on cancer cells, the stimulation of tumor cell growth can also be indirectly mediated through growth factors and receptors such as insulin-like growth factor 1 (IGF-1). Increased cancer risk is also associated with increased adipose tissue, such as in abdominal obesity, due to the higher risk of insulin resistance and hyperinsulinemia. Waist circumference is a parameter that indicates an individual’s level of adiposity. In addition, the risk of cancer also increases in the elderly as they age. This study aims to assess the correlation between waist circumference and IGF-1 levels in the elderly population in Bali, Indonesia. Methodology. This study used a cross-sectional analytical design conducted in the Melinggih Village, Gianyar Regency. The study was conducted in September 2023. This study has been approved by the Research Ethics Commission number 2020/UN14.2.2.VII.14/LT/2023. The study population included elderly individuals residing in the Melinggih Village who were willing to participate. Data analysis encompassed descriptive analysis and the Spearman correlation test. Result. A total of 88 subjects participated in the study, consisting of 57 females (64.8%) and 31 males (35.2%). A statistically significant but weak correlation coexists between waist circumference and IGF-1 levels. Conclusion. A weak but statistically significant positive correlation was found between waist circumference and IGF-1 levels in the elderly. However, because of the small sample size, another study with a bigger sample size with enough power to investigate this association needs to be done to validate the results of the current study.